Ball-milled synthesis of biochar-MOF nanocomposite for the concurrent recovery of mixed contaminants from wastewater - Sefiu Olaitan Amusat; Temesgen Girma Kebede; Edward Ndumiso Nxumalo; Simiso Dube; Mathew Muzi Nindi (Results in Chemistry)
In this study, a biochar-metal–organic framework (MOF) nanocomposite was synthesized via ball milling to enable the simultaneous extraction of multiple contaminants from wastewater. The Brunauer-Emmett-Teller (BET) analysis revealed a significant increase in surface area after ball milling. SEM-EDS confirmed the successful synthesis, while X-ray diffraction (XRD) and thermogravimetric analysis (TGA) indicated an amorphous structure with thermal stability up to 300 °C. FTIR and XPS analyses identified functional groups such as C=C, C-H, –COOH, C=O, –OH, C-O, and Fe-BTC. Adsorption capacity and binding properties were evaluated using Langmuir and Freundlich isotherms, with the Freundlich model providing a better fit (R2 = 0.9579–0.9913) compared to the Langmuir model (R2 = 0.9239–0.9862). The nanocomposite exhibited maximum adsorption capacities of 74.18–85.69 mgg−1 for heavy metals and 72.99–86.21 mgg−1 for steroidal hormones. Kinetic analysis showed the adsorption process followed a pseudo-second-order model. A leaching test confirmed the nanocomposite’s high stability, making the BC-Fe-BTC nanocomposite a promising material for wastewater treatment applications.